INFLUENCE OF THE ELECTROMAGNETIC RADIATION OF MOBILE COMMUNICATION DEVICES ON THE ORGANISM OF A HUMAN BEING - Krushevskyy, Yuriy; Kravtsov, Yurij; Boroday, Yaroslav (Scientific Works of Vinnytsia National Technical University, 2015)
The paper considers elaborated methods of the calculation of the human organism radiation intensity by the aerials of the base stations of the cellular communication and the approximated calculation of the time of the safe usage of a mobile phone. The paper contains the examples of the calculations.